A promising non-transformable tetragonal YSZ nanostructured feedstocks for plasma spraying-physical vapor deposition. Issue 1 (January 2018) - Zhou, Feifei; Wang, You; Wang, Yaming; Wang, Liang; Gou, Junfeng; Chen, Wenlong
Abstract: The nanostructured 8 wt% yttria stabilized zirconia (n-8YSZ) feedstocks used for plasma spraying-physical vapor deposition (PS-PVD) were successfully prepared by the powder reconstitution method for the first time in this study. The n-8YSZ feedstocks were characterized by TEM, SEM and XRD. The results reveal that the grain size of n-8YSZ feedstocks is below 20 nm and the particle size of spherical or equiaxed agglomerates is below 23 µm. The n-8YSZ feedstocks are composed of only tetragonal prime (t´) phase. The t´ phase of feedstocks would bring excellent thermal shock resistance in the coatings. Hence, the n-8YSZ feedstocks will have a broader application prospect than the commercial M6700 powders whose main phase composition is monoclinic zirconia used for PS-PVD.